Nesting habitat of Chubut Steamer Ducks in Patagonia, Argentina - Agüero, Maria Laura (2010)
We studied nest-site selection of the flightless Chubut Steamer Duck (Tachyeres leucocephalus) along 292km of continental coastline and 59km of island coastline in Patagonia, Argentina, between 2004 and 2006. This area encompasses the main breeding range of the species. Almost all nests were on islands and islets, which ranged in area from 0.5 to 54.4ha and were 0.01-5.6km from the mainland. Nesting sites were within bays and inlets with shallow waters and protected from waves, winds and strong currents. Using logistic regression analyses in an information-theoretic framework to compare habitat characteristics between nesting sites and randomly chosen sites, we found that Chubut Steamer Duck nesting sites were strongly and positively associated with higher proportions of shrub vegetation cover. To a lesser degree, the percentage of silt-clay sediment was also positively associated with nesting sites. Nest-site selection is thought to be associated with concealment from aerial predators and protection from weather. This is the first study of breeding habitat and nest-site selection of Chubut Steamer Ducks, and will contribute to management and habitat conservation for this rare flightless duck through identification of both general and specific habitat features that should be preserved or enhanced.